Atividade de compostos Quitosânico-Guanilados contra a formação de biofilme de isolados clínicos de Pseudomonas aeruginosa - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
Pseudomonas aeruginosa is considered one of the main etiological agents in infectious processes in the hospital environment. It is an opportunistic pathogen with a considerable level of antimicrobial resistance. With the decreasing effectiveness of antimicrobials available in medical practice, there is a growing demand for innovative compounds for antimicrobial treatment. In this context, the investigation of biomaterials such as chitosan, which is a polysaccharide obtained by the deacetylation of chitin and which has interesting physicochemical and biological properties, represents an interesting alternative due to the low propensity of microorganisms to develop resistance, in addition to the polymer and be biocompatible, renewable and biodegradable. One of the limiting factors of its use is its low solubility under physiological conditions. However, chitosan can acquire new properties when structurally modified, expanding its uses according to the group attached to it. This work aimed to evaluate the biological properties of chitosan and chitosan-guanylated derivatives with the evaluation of toxicity with Artemia salina lethality assay and study of the antimicrobial activity with the determination of the minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC). Subsequently, the profile of biofilm formation by clinical isolates of P. aeruginosa and the effect of subinhibitory concentrations of compounds on biofilm formation by these bacteria were evaluated. The results showed that the tested compounds did not show toxicity to A. salina with LC50 above 1000 µg.mL-1 . Regarding the antimicrobial activity, chitosan presented MIC from 1.25 to 2.5 mg.mL-1 and with CMB > 2.5 mg.mL-1 . The most active guanylated chitosans against P. aeruginosa were compounds 3b and 3c with MIC of 0.625mg.mL-1 . Chitosan did not demonstrate bactericidal activity against P. aeruginosa isolates at the concentrations tested, with CMB > 2.5 mg.mL-1 . The most active compound was derivative 3b with CMB of 0.625 mg.mL-1 against P. aeruginosa ATCC 27853 and ranging from 1.25 to > 2.5 mg.mL-1 for the other isolates. Biofilm formation was observed in 13 P. aeruginosa, 6 were classified as strong formers, 4 as moderate formers and 3 as weak formers. The effect of the compounds on biofilm formation was variable in the 9 isolates tested. Chitosan provided a slight decrease in viable cells in biofilms in 77.78%, while chitosan-guanylated 3a and 3b decreased biofilm in 66.66% and 33.33% of the isolates, respectively. The chitosan-guanylated derivatives did not show significant improvement in their solubility characteristics at physiological pH in relation to chitosan. Chitosan and guanylated-chitosans showed a low degree of toxicity and low activity against biofilm formation by clinical isolates of P. aeruginosa. Further studies should be performed to corroborate our findings.
Activity of Chitosan-Guanylated compounds against biofilm formation of clinical isolates of Pseudomonas aeruginosa
Keywords: Quitosana; Guanidina; Quitosana guanilada; Atividade biológica; Toxicidade; Atividade antimicrobiana; Pseudomonas aeruginosa; Chitosan; Guanidine; Guanylated chitosan; Biological activity; Toxicity; Antimicrobial activity; OUTROS